Renewing Experience - Therapists’ Thoughts on What is Effective in Psychotherapy - Lindgren, Ola; Folkesson, Per; Almqvist, Kjerstin (European Journal for Qualitative Research in Psychotherapy, 2012)
In this qualitative study, nine psychotherapists with different theoretical approaches were interviewed about their thoughts on what is effective in their work. Data was collected and analyzed according to Grounded Theory. The results are presented as a grounded theory of therapists’ thoughts on what is effective in psychotherapy. The theory consists of a core category, Renewing Experience, its subcategories and their subsequent properties. The therapists’ efforts in psychotherapy are to use the relationship with the patient as well as psychotherapy techniques available to cause the patient to experience something new. New experiences in psychotherapy add to and place earlier life experiences in a new perspective. If the new experiences are related to the patient’s central issues, they can modify and renew existing and maladaptive conceptions of reality and make new life alternatives available to patients. Renewing Experience is a cumulative process where the therapist’s ability to individualize interplay is decisive. The function of the therapist in psychotherapy has been discussed and examined in research to some extent. The therapist-patient relationship, for example (Norcross, 2002), is one area in which the therapist as an individual has been of interest. In a summary of sixty years of psychotherapy research, Lambert and Barley (2002) state that the therapeutic relationship is of greater importance for the outcome of therapy than the chosen techniques; and that some therapists therefore are better than others in helping patients. Those therapists are reported as being more understanding and empathic, warmer and more supportive, and to a certain extent, less blaming and critical of their patients. A similar line of research involves the importance of the therapeutic alliance (Horvath & Bedi, 2002), a concept that summarizes various aspects of how well therapist and patient manage to find common goals and a mutual commitment to the therapy process. Horvath and Bedi conclude that a strong therapeutic alliance helps the patient stay in therapy and contributes to a positive outcome both statistically and clinically. Therapists who correctly are able to perceive the degree of alliance early in therapy and respond ad- equately to patient needs are more likely to be successful. Psychotherapy research has traditionally identified separate common and specific factors that are helpful in psychotherapy. Common factors , relationship factors, are considered to be present in all psychotherapies and specific factors, the therapeutic models and techniques, are the active ingredients that are found exclusively in a certain technical intervention or theoretical orientation. A some- what different approach (Duncan, Miller, Wampold, & Hubble, 2010) is the use of the concept therapeutic factors for all effective interventions regardless of whether they are considered common or specific. This view acknowledges that different working factors or mechanisms in psychotherapy are intertwined and interactive and that it is not meaningful to single out certain aspects of psychotherapy as more specific or more effective than others. Specific technical interventions are often the trademarks of a thera- peutic school or orientation. They, however, rely on the existence of a safe and trusting therapeutic relationship as well as a skilled and fine-tuned psychotherapist in order to have a therapeutic effect (Lindgren, Folkesson, & Almqvist, 2010). Another line of research that focuses upon psychotherapists and their use of theory and techniques is the study of private theories. Private theories are defined by Werbart and Levander (2006) as therapists’ pre-conscious explanatory systems. Werbart and Levander attribute the creation of these theories to the therapist’s psychological need of coming to an understanding of the patient’s problems and how the problems can be solved. According to Canestri (2006), private theory is the therapist’s elaboration upon official theory in light of experiences with patients as well as the need for guidance in individual cases. Private theories constantly change and evolve, influenced by theories outside the therapist’s official theoretical orientation as well as by clinical practice and experience with pa- tients. This process is common and more or less unavoidable according to Canestri. When private theories areA meta-analysis of internet-based Cognitive Behavioral Therapy also demonstrates that therapy techniques do not work properly without the personal input of a therapist who engages in a patient-therapist dialogue via e-mail to assist in the application of the techniques (Spek, et al., 2006). Internet interventions that include access to therapist support are far more efficient than interven- tions lacking access to such support. Patients in Internet treatment seem to be able to benefit highly from the limited support they receive through e-mail communication with the therapist. generalized and published for example as case studies, they impact the therapeutic community in a more general sense and may eventually lead to changes in official theories. Sandler (1983) argues that the official theories are general by nature and need to be more specific to become applicable to an individual case. There are gaps in official theories that need to be filled by a therapist in order to treat a patient. Creating private theories is one way in which the therapist achieves this theoretical specificity. Thus, many actions and decisions taken by therapists seem to rely not only on theoretical knowledge, but also on therapists’ experi- ences and elaborations of their own concepts of psychotherapy as well as their thoughts about psychotherapy and what works. In this study we aim to explore, in some depth, what therapists think about their own personal ways of doing therapy and how they describe, in their own words, what they do as therapists in their daily work with patients. The thoughts and reflections we are most interested in are those emanating from their own clinical work. Psychotherapy, after all, is an inter-subjective experience (Elliott & James, 1989).